2023
DOI: 10.3390/f14020260
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Diversity in the Link between Tree Radial Growth and Remote Sensing Vegetation Index of Qinghai Spruce on the Northeastern Margin of the Tibetan Plateau

Abstract: Global warming is causing some regions to experience frequent and severe drought, with important impacts on montane forest vegetation. In this study, the Qilian Mountains is on the northeastern margin of the Tibetan Plateau which was divided into three study areas, the eastern (HaXi), middle (XiShui) and western (QiFeng) parts. This work focused on interannual trend comparison of tree-ring width (TRW) and enhanced vegetation index (EVI), their relationship characterization from 2000 to 2020, and spatial and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…However, our findings of two spectral vegetation indices, EVI and VARI, may offer key indices to detect trees that are under water-stressed conditions, causing changes in the physiological and biochemical processes in trees. For example, Wei et al (2023) found a positive correlation between spatial and temporal variations of tree-ring width (TRW) and the Enhanced Vegetation Index (EVI). The relationship between the TRW and EVI became stronger in more arid regions where trees were under more drought and subsequent water-stress conditions (Wei et al, 2023).…”
Section: Limitations Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…However, our findings of two spectral vegetation indices, EVI and VARI, may offer key indices to detect trees that are under water-stressed conditions, causing changes in the physiological and biochemical processes in trees. For example, Wei et al (2023) found a positive correlation between spatial and temporal variations of tree-ring width (TRW) and the Enhanced Vegetation Index (EVI). The relationship between the TRW and EVI became stronger in more arid regions where trees were under more drought and subsequent water-stress conditions (Wei et al, 2023).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…For example, Wei et al (2023) found a positive correlation between spatial and temporal variations of tree-ring width (TRW) and the Enhanced Vegetation Index (EVI). The relationship between the TRW and EVI became stronger in more arid regions where trees were under more drought and subsequent water-stress conditions (Wei et al, 2023).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…They also play an indispensable role in maintaining the ecological safety of the Asian water tower and the upper of the Yangtze River [35]. Spruce forests, with their narrower ecological amplitude and sensitivity to climate change [36,37], are among the most threatened in the context of global warming, especially in the highly climatesensitive region of the Tibetan Plateau [38][39][40]. Therefore, it is of great research importance to recognize the variations in the suitable distribution pattern of endangered spruce on the Tibetan Plateau.…”
Section: Introductionmentioning
confidence: 99%